PENGARUH DUKUNGAN ATASAN DAN PEMBERDAYAAN TERHADAP KEPUASAN KERJA DENGAN DIMEDIASI KARIR PLATEAU (STUDI PADA BADAN PEMBERDAYAAN PEREMPUAN DAN KELUARGA BERENCANA KAB. PATI) - Wisnu Ardiyanto, 12.42.02.0009 (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to determine the effect of supervisor support and empowerment of career plateau with the mediation of job satisfaction (Studies in BPPKB Kabupaten Pati ) " . Population in the study were employees in the BPPKB Kabupaten Pati much as 135 people . Sampling technique using purposive sampling as many as 130 employees . A statistical technique used is validity test with matrix componen, reliability test with alfa cronbach, double regresion analisis , t test and r2 test with adjusted r square. Results reveal that supervisor support significantly negative effect on career plateau. Empowerment significant negative effect on career plateau. Supervisor Support positive influence significant job satisfaction. Empowerment significant positive effect on job satisfaction. Career plateau significant negative effect on job satisfaction. Career plateau mediate the influence of supervisor support on job satisfaction. Career plateau is not mediating variables empowerment on job satisfaction. Keywords : Supervisor Support , Empowerment , Career Plateau and Job Satisfaction